Quantum Recitation Therapy in Syair Nasihat as an Alternative to Strengthen Mental and Spiritual Efforts during and Post- Pandemic Covid 19 - Wirajaya, Asep Yudha; Sudardi, Bani; Istadiyantha, Istadiyantha; Warto, Warto (Javanologi: International Journal of Javanese Studies, 2021)
Syair Nasihat (SN) is a classic Malay literary work written using Arabic letters/characters and in Malay. This SN contains various kinds of advice for humans to be able to achieve the happiness of life, both in this world and in the hereafter. This teaching is still considered very relevant to human life in the postmodern era, which is even further away from religious values. As a result, it is difficult for humans to find true happiness in every episode of their life. Therefore, a study on SN needs to be done so that postmodern humans can at least get inspiration to be able to find true happiness in the process of life. The research method used is the philological method. This method is intended so that researchers can present good and correct text edits. Furthermore, the edits are studied with content analysis, particularly those related to the quantum concepts of dhikr. The concept of quantum dhikr therapy is contained in the SN text, namely (1) oral dhikr; (2) heart remembrance; (3) mind remembrance; and (4) deeds dhikr. This quantum dhikr study is expected to provide an overview and simultaneously convince readers/connoisseurs of SN about the potential of dhikr that can be used as an alternative to strengthen mentally and spiritually, both during the Covid 19 pandemic and post-pandemic.